Efektivitas Metode Earned Value dalam Proyek Pengaman Pantai - Farizal, Teuku; Jovanka Akhuya, ratu ratu; Febrianti, Dian (JTERA (Jurnal Teknologi Rekayasa), 2024)
Coastal erosion threatens coastal areas, making coastal protection projects crucial. This study evaluates the performance of a coastal protection infrastructure development project in Kampung Pasir Village, West Aceh, which faces the challenges of a dynamic marine environment and the demands of timeliness and budget adherence. The Earned Value method, with analysis of BCWS, BCWP, SV, SPI, and TE, is used to measure project performance. The results show an 11-week delay at the beginning (negative SV), but the project managed to surpass the schedule with an SPI value reaching 1.35 in the 12th week, indicating a 35% progress acceleration and an estimated faster completion. This acceleration is supported by the focus of activities on the material fabrication stage at the beginning of the project, which is then followed by the installation of concrete on site. This study recommends the application of the Earned Value method to facilitate monitoring, deviation identification, and optimization of coastal protection project performance. Further research can explore the integration of environmental risk factors and community participation in project performance analysis.